OPTIMIZATION OF OIL FIELD DEVELOPMENT PROCESS BASED ON EXISTING FORECAST MODEL - Lushpeev, Vladimir; Margarit, Andrey (Journal of Applied Engineering Science, 2018)
Process of oil-and-gas field development optimization under the conditions of a mineral raw material base deterioration and increase in a share of hard-to-recover reserves is the integral part of commercial production stage, especially in the last stage of development. Decisions regarding the optimization of the development system with contour water flooding under the conditions of a high water-cut of well production need to be made using additional instruments for the decision making, such as 1-D, 2-D and 3-D models. Using of simulation does not exclude a participation of experts in such work and imposes great responsibility on them in making decisions. Searching for optimal decisions under the oil-and-gas field development optimization based on physic-mathematical models together with the participation of recovery and development experts is the basis for managerial decision making in oil-and-gas production companies. This article shows the principles of the oil-and-gas field development optimization based on the existing forecast model and describes an industrial example of such optimization instrument usage together with the participation of the experts.
Keywords: oils; Optimizer; development processes; oil field